1994
DOI: 10.1088/0953-4075/27/14/021
|View full text |Cite
|
Sign up to set email alerts
|

Ion mobility measurements for O2+in helium gas at 4.35 K

Abstract: The mobility of O2+ in He has been measured using a liquid helium cooled, selected ion drift tube at 4.35 K. The dependence of mobility on effective temperature, for O2+, is similar to that measured previously for rare gas ions moving in He. The mobility reaches a maximum at between 500 K and 600 K where it is in reasonable agreement with the existing room temperature measurements. Below 70 K there is a region in which mobility is constant, but lower than the polarization limit, and below 10 K, mobility decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, when seeding the drift tube with H + 3 ions, they observed strong signals from HHe + N and H 3 He + N , as well as a weaker contribution from H 2 He + N (3 ≤ N ≤ 10) clusters. The method of producing Hesolvated ions in cooled, high pressure drift tubes was in subsequent years successfully applied to other small molecular systems like N + 2 , O + 2 , and CO + [120,273,274]. An alternative approach developed at Yamanashi University in Japan used a pulsed electron beam mass spectrometer with the ion source mounted to a cryocooler [222,275].…”
Section: Other Experimental Workmentioning
confidence: 99%
“…However, when seeding the drift tube with H + 3 ions, they observed strong signals from HHe + N and H 3 He + N , as well as a weaker contribution from H 2 He + N (3 ≤ N ≤ 10) clusters. The method of producing Hesolvated ions in cooled, high pressure drift tubes was in subsequent years successfully applied to other small molecular systems like N + 2 , O + 2 , and CO + [120,273,274]. An alternative approach developed at Yamanashi University in Japan used a pulsed electron beam mass spectrometer with the ion source mounted to a cryocooler [222,275].…”
Section: Other Experimental Workmentioning
confidence: 99%
“…14,15 The earliest drift tube with liquid helium cooling had been developed by Böhringer and Arnold to obtain data mainly on ion-molecule reaction rates. 16 The lowest gas temperature in this apparatus was about 20 K, which is much higher than the boiling point of helium 4.22 K. Our previous apparatus, which have a drift tube 100 mm in length, had allowed us to operate at 4.4 K. Using this setup, we have reported the drift velocity of ions in helium gas at 4.4 K [17][18][19][20][21] and the formation of helium cluster ions, [22][23][24][25][26] in which helium atoms might be surrounding an ionic core.…”
Section: Introductionmentioning
confidence: 94%
“…11 In 1992, Kojima et al 12 found that the thermal transpiration effect had to be considered carefully in ion mobility measurements at liquid nitrogen and helium temperatures using a drift tube mass spectrometer, and that the correction method proposed by Takaishi and Sensui could apply to calibrate the helium gas pressure in the drift tube. Also, in our previous works on the ion mobility and the three-body ionatom association reaction rate, [13][14][15][16] it was impossible to obtain reliable results at gas temperature of 4.4 K without pressure correction by the Takaishi-Sensui formula.…”
Section: Introductionmentioning
confidence: 97%